What happens to DNA data of millions as 23andMe files bankruptcy? - Geoff Bennett (2025)
The bankruptcy of 23andMe is raising concerns about the future of its DNA information. Once a pioneer in the genetic testing industry, the company faced backlash after hackers leaked user data in 2023. Now, millions could see their genetic data dealt in a potential sale.